2016
DOI: 10.1016/j.actamat.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained elastodynamics of fast moving dislocations

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 101 publications
1
30
0
Order By: Relevance
“…The CAC method has been demonstrated to be able to predict the dynamics of dislocations [31][32][33][34][35] and fracture [2,36,37], and to reproduce full sets of phonon branches in both atomistic and coarse-grained regions [38] above the wavelength of coarse-grained elements.…”
Section: The Cac Methods and Wave Reflections At The A-c Interfacementioning
confidence: 99%
“…The CAC method has been demonstrated to be able to predict the dynamics of dislocations [31][32][33][34][35] and fracture [2,36,37], and to reproduce full sets of phonon branches in both atomistic and coarse-grained regions [38] above the wavelength of coarse-grained elements.…”
Section: The Cac Methods and Wave Reflections At The A-c Interfacementioning
confidence: 99%
“…For monoatomic face-centred cubic (FCC) crystals, three options are shown in figure 2 with each containing only one atom and having the same volume. They are (a) the Wigner-Seitz cell which is the primitive unit cell widely used in solid-state physics, (b) the rhombohedral shaped unit cell which is the primitive unit cell primarily used in the concurrent atomistic-continuum (CAC) method for modelling of FCC crystals [55][56][57][58][59][60][61][62][63] and the rectangular prism which is the only unit cell for FCC crystals whose faces are mutually orthogonal. Recall that the stress tensor defined by Cauchy is the 'the force per unit area on three given rectangular planes' [19].…”
Section: Numerical Methods For Local Stress Calculationmentioning
confidence: 99%
“…The CAC method can be used to complement MD to provide this information. A verification study of the CAC method in modeling fast moving dislocations has been reported 74 . One of our recent works has presented a phonon pulse propagation in crystalline materials with a fast moving dislocation and dislocation array while studying the effect of phonons on dislocation mobility 75 .…”
Section: Phonons Scattering By Moving Dislocationsmentioning
confidence: 99%